The Effect of Human Resources Quality and Work Professionalism on Employee Performance at UD. Nacen Rupat Serdang Bedagai - Hadi Panjaitan (PT Inovasi Pratama Internasional, 2022)
This study aims to determine whether the quality of human resources, work professionalism has a significant influence on employee performance at UD. Nacen Rupat Serdang Bedagai. T e knik a n a lis d a ta which will be used by the author in this study is to use SPSS software version 18 with statistical techniques. Statistics play an important role in research, both in modeling, in formulating hypotheses, in developing data collection tools and instruments, in preparing research designs, in determining samples, and in data analysis. The t-count value of the HR quality variable (X1) is 19.360, thus t-count < t table, then H0 is accepted and H1 is rejected, which means that the HR quality variable (X1) has a significant effect on performance. The t-count value of the work environment variable (X2) is 0.156, thus t-count > t table, then H0 is rejected and H1 is accepted, which means that the work professionalism variable (X2) has no significant effect on performance. The calculated F value is 187.496 while the F table value is 3.44. Thus, F count > F table means that the variables of HR quality and work professionalism together have a positive and significant effect on performance. The variables of human resource quality and work professionalism contribute to the influence of performance by 94.5%. This result is the result of (R 2 x 100%), while the remaining 5.5% is influenced by other variables not examined in this study.